Efektivitas Nasionalisasi dalam Menyeimbangkan Kepentingan Nasional dan Investasi Asing di Indonesia - Rahely, Angela; Broto Hazelli Elfrida, Adi; Hamidah, Abna (Recital Review, 2025)
The nationalization of foreign-owned companies in Indonesia, from the early independence period to the present, has sparked debates between national interests and the protection of foreign investors. On the one hand, nationalization is considered an essential instrument to strengthen economic independence and state sovereignty. On the other hand, poorly regulated nationalization practices without clear procedures, adequate financing schemes, and proper investor protection mechanisms may lead to legal uncertainty and a decline in the investment climate. This study aims to analyze the effectiveness of nationalization in Indonesia by examining three main aspects: legal procedures, compensation financing schemes, and the protection of foreign investors. Using a normative juridical method based on literature review, the study finds that although the legal framework of nationalization is stipulated under the Investment Law, its implementation remains hampered by lengthy procedures and ambiguities regarding the definition of “national interest.” Moreover, the financial burden of compensation often disrupts the country’s fiscal stability. The findings highlight the urgency of regulatory reform to ensure that nationalization can be carried out effectively, fairly, and in balance—protecting national interests while maintaining legal certainty for foreign investors.